Assessment of nitrogen hotspots induced by cropping systems in the Bohai Rim region in China by integrating DNDC modelling and the reactive nitrogen spatial intensity (NrSI) framework - Qingmei Wang; Xia Liang; Yingchun Wang; Ligang Wang; Arvin R Mosier; Deli Chen (Environmental Research Letters, 2020)
More than half of nitrogen (N) inputs to cropland are lost to the environment via denitrification, ammonia (NH _3 ) volatilization, nitrate leaching and surface runoff. Cropping systems are, therefore, a large contributor to reactive N (Nr, all species of N except N _2 ) losses. The Nr spatial intensity (NrSI) framework was developed to quantify the environmental burdens due to Nr losses on a per area basis. However, the current application of the NrSI framework is limited by the development of virtual N factors (VNFs, Nr released to the environment per unit of Nr consumed) for agricultural products and it could not differentiate pathways of Nr losses linked to consequences in various environmental media. As the Denitrification-Decomposition (DNDC) model is capable of tracking N fluxes across cropping systems and regions, we integrated the DNDC model and the NrSI framework to identify hotspots of Nr losses induced by cropping systems, and illustrate the approach with a case study for the Bohai Rim region (BR) in China. Altogether 29 types of cropping systems (i.e. 16 mono, 10 double and 3 triple cropping systems) in 429 counties were simulated for the N balance, Nr losses and the NrSI associated with crop production. Regarding the total Nr losses in the BR, 45% of the total N input was lost to the environment during crop production with NH _3 volatilization and nitrate leaching the two main pathways, making up 24% and 19% of the total N input, respectively. Shandong province was the biggest contributor of the total Nr losses (45.6%) among regions, and winter wheat-summer maize, triple vegetable and spring maize cropping systems were the top three contributors among various cropping systems. For Nr loss hotspots, there are substantial variations of NrSI across cropping systems (41–1024 kg N ha ^−1 y ^−1 ) and counties (28–4782 kg N ha ^−1 y ^−1 ). Beijing had the highest NrSI associated with crop production (307 kg N ha ^−1 y ^−1 ) among regions, and vegetable systems had the highest NrSI of 355 kg N ha ^−1 y ^−1 among cropping systems. The application of this integrated method is useful to identify areas and/or cropping systems with particularly high Nr losses and NrSI to provide basic information for setting Nr mitigation priorities on a wide range of regions and cropping systems.